Nager Acrofacial Dysostosis Syndrome: A Newborn with Bilateral Hearing Impairment - Naher, Begum Sharifun; Mannan, Md Abdul; Noor, Khaled; Shahidullah, Md (Bangladesh Journal of Child Health, 2012)
DOI: http://dx.doi.org/10.3329/bjch.v34i2.10220 BJCH2010; 34(2): 67-69